Non‐Fragile Saturation Controller for Fractional‐Order Permanent Magnet Synchronous Generator With Fuzzy Quantized Mechanism - Dineshkumar, Chendrayan; Hoon Jeong, Jae; Hoon Joo, Young (International journal of adaptive control and signal processing, 2025)
ABSTRACT The main objective of this study is to develop a non‐fragile saturation controller for a fractional‐order (FO) permanent magnet synchronous generator (PMSG) and utilize a fuzzy quantized mechanism. To this end, first, fractional‐order control is introduced into the non‐linear PMSG model to improve the convergence rate beyond the existing integer‐order control techniques. Next, the non‐linear PMSG model is converted to linear sub‐models using the Takagi‐Sugeno (T‐S) fuzzy method. Utilizing refined sector conditions, we conduct a theoretical analysis of the Mittag‐Leffler (M‐L) stabilization for the resultant closed‐loop systems. This analysis employs certain inequality techniques applied to the M‐L function and FO Lyapunov theory. Moreover, based on the polytopic representation approach, sufficient conditions ensuring M‐L stabilization are established by a closed‐loop system. Furthermore, we have devised two separate convex optimization approaches to effectively reduce the actuator costs and expand the admissible initial region (AIR). Finally, the method proposed in this study demonstrates the superiority and efficiency of the derived results. This study introduces a non‐fragile saturation controller for a fractional‐order permanent magnet synchronous generator (FO‐PMSG) with a fuzzy quantized mechanism. By employing refined sector conditions and the Takagi‐Sugeno fuzzy method, the proposed approach ensures Mittag‐Leffler (M‐L) stabilization while optimizing actuator costs and expanding the admissible initial region. Theoretical and simulation results confirm the effectiveness of the proposed controller in achieving superior stability and performance compared to existing methods.